A survey of college students’ willingness to participate in social practice with perceived environmental support based on the applied mixed research method - Li, Yingxin; Jin, Zhou; Dong, Gaoqi; Zheng, Ran; Wang, Ting (Frontiers in Psychology, 2022)
Contemporary social reform is constantly promoting rapid social transformation, and social practice has a special educational function in higher education. However, research shows that college students’ willingness to participate in social practice is weak. Using the mixed research method, 438 completed questionnaire surveys on perceived environmental support were collected from college students. The influence of perceived environmental support on Chinese college students’ willingness to participate in social practice was analyzed using the partial least squares structural equation modeling method, and an empirical test was conducted. The findings are as follows. (1) Perceived environmental support has a significant impact on students’ participation attitude and perceived behavioral control. (2) Participation attitude and perceived behavior control have significant influence on participation intention, but behavioral norms have no significant influence. (3) Participation intention and perceived behavioral control have significant influence on actual behavior. This study provides the theoretical basis of perceived environmental support for future research on social practice participation intention and offers some theoretical guidance for the implementation of social practice in China.